Hot isostatic pressing of multifilamentary MgB2 wires in solid state media for large scale application. (12th February 2015) - Cetner, T; Morawski, A; Gajda, D; Häßler, W; Rindfleisch, M; Tomsic, M; Zaleski, A; Czujko, T; Żuchowska, E; Przysłupski, P
Abstract: Multifilamentary MgB2 wires were annealed under the high pressure of low-friction, solid state media such as BN and graphite powders. The idea was to replace the hot isostatic pressing in argon medium, which is beneficial to wires transport properties but is difficult for application on an industrial scale. The experimental results show that annealing in BN or graphite under 200 MPa leads to enhancement of the critical current, similar to that observed earlier for high pressure argon annealing. An unwanted effect of the process is the flattening of the round wires, which after the treatment yields an elliptical cross section with b to a ratio of around 85 ± 5%. Comparison of critical currents and microstructure of samples synthesized with different parameters are presented.